Sliding parts

By applying a graphite-based thin film with fillers directly to the SiC substrate of sliding parts, the challenges of achieving stable low friction across diverse conditions are addressed, resulting in enhanced wear resistance and foreign matter resistance.

JP7661481B2Active Publication Date: 2025-04-14EAGLE INDS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023510942
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2022-03-17
Publication Date
2025-04-14
Estimated Expiration
2042-03-17

AI Technical Summary

Technical Problem

Existing sliding parts, such as those used in mechanical seals, face challenges in achieving stable low friction effects across a wide range of use conditions, particularly in non-lubricated environments where foreign matter resistance and wear resistance are compromised.

Method used

The sliding parts are coated with a thin film mainly made of graphite, which includes a filler with dimensions equal to or smaller than the film thickness. This thin film is directly applied to the SiC substrate, providing self-lubrication and enhancing wear resistance and foreign matter resistance.

Benefits of technology

The graphite-based thin film with fillers achieves stable and low friction effects in various environments, including fluid lubrication, boundary lubrication, and non-lubrication conditions, while preventing damage to the sliding surface due to friction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661481000003
    Figure 0007661481000003
  • Figure 0007661481000004
    Figure 0007661481000004
  • Figure 0007661481000005
    Figure 0007661481000005
Patent Text Reader

Abstract

Provided is a sliding component with which it is possible to obtain a low friction effect that is stable under a wide range of usage conditions. A sliding component 10, 20 having sliding surfaces 11, 21 that slide in a relative manner, wherein a base material 22 of the sliding component 20 is directly coated with a thin film 30 mainly composed of graphite, the sliding surface 21 is formed from the thin film 30, and the thin film 30 contains fillers 40, 41 having a film thickness the same or smaller than that of the thin film 30.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a sliding part that slides relative to one another, and relates to a sliding part used in a shaft sealing device that seals the rotating shaft of a rotating machine in, for example, an automobile, general industrial machinery, or other sealing fields, or a sliding part used in a bearing of a machine in an automobile, general industrial machinery, or other bearing fields. [Background technology]

[0002] Sliding components have a sliding surface that slides relative to a mating sliding surface, and are used as components of bearings that support rotating or reciprocating shafts, etc., and shaft sealing devices that prevent leakage of sealed fluids. As a shaft sealing device that prevents leakage of sealed fluids, for example, a mechanical seal is equipped with a pair of annular sliding components that rotate relative to each other and whose sliding surfaces slide against each other. For example, the sliding component shown in Patent Document 1 is made of carbon, a soft material, and is designed to achieve low friction by utilizing the self-lubricating properties of carbon. However, if foreign matter enters between the sliding surfaces, the sliding surface of the sliding component made of carbon is easily scraped, resulting in problems with foreign matter resistance. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-58517 A (page 6, Figure 1) [Patent Document 2] JP 2004-225725 A (page 6, Figure 2) Summary of the Invention [Problem to be solved by the invention]

[0004] Forming sliding components from the hard material SiC (see, for example, Patent Document 2) can improve foreign matter resistance. However, for example, when a mechanical seal is used in an unlubricated environment (i.e., a dry environment) without any liquid between the sliding surfaces, the high friction coefficient of SiC in air can lead to the risk of galling on the sliding surfaces depending on the operating conditions. Furthermore, in Patent Document 2, the sliding surfaces of the sliding components are coated with a diamond-like carbon coating (hereinafter sometimes referred to as a DLC coating). For example, when used in an unlubricated environment, the high hardness of the DLC coating can lead to galling on the mating sliding surface depending on the operating conditions. To achieve the low-friction effect of the DLC coating, complicated conditions must be set, such as changing the hydrogen content of the DLC coating depending on the operating conditions, which limits its versatility.

[0005] The present invention has been made in view of these problems, and has as its object to provide a sliding component that can provide a stable low-friction effect over a wide range of use conditions. [Means for solving the problem]

[0006] In order to solve the above problems, the sliding component of the present invention comprises: A sliding component having a sliding surface that slides relative to one another, The substrate of the sliding component is directly coated with a thin film mainly made of graphite, the sliding surface is made of the thin film, and the thin film contains filler having dimensions equal to or smaller than the thickness of the thin film. According to this, by coating the substrate of the sliding component with a thin film mainly made of graphite and containing a filler, the thin film mainly made of graphite that constitutes the sliding surface is sheared between the graphite layers that are bonded by van der Waals forces due to friction with the sliding surface of the counterpart, and part of the thin film remains in the fine recesses on the substrate surface, smoothing the sliding surface and allowing the self-lubricating properties of the graphite to be exhibited against the sliding surface of the counterpart, thereby achieving a stable low-friction effect over a wide range of usage conditions, such as in the hydrodynamic lubrication region, boundary lubrication region, and non-lubricated environments. In addition, the sliding surface is given the function of the filler, and even in a thin thin film, the filler is less likely to fall off and is also less likely to protrude from the sliding surface, making it less likely to damage the sliding surface of the counterpart due to friction.

[0007] The thin film may contain a high-hardness filler that is harder than the graphite that constitutes the thin film. According to this, the thin film mainly made of graphite contains a high-hardness filler, so that the wear resistance and foreign matter resistance of the sliding surface can be improved.

[0008] The hardness of the high-hardness filler may be lower than the hardness of the mating sliding surface. According to this, since the high-hardness filler is softer than the mating sliding surface, the mating sliding surface is less likely to be damaged by friction.

[0009] The thin film may contain a low-friction filler having a friction coefficient smaller than that of the graphite constituting the thin film. According to this, the thin film mainly made of graphite contains a low-friction filler, thereby making it possible to enhance the lubricity of the sliding surface. [Brief explanation of the drawings]

[0010] [Figure 1] 1 is a vertical cross-sectional view showing an example of a mechanical seal according to an embodiment of the present invention. [Figure 2] FIG. 4 is an enlarged cross-sectional view showing the sliding surface of the rotary seal ring on which a thin film is formed before use in the example. [Figure 3]FIG. 2 is a cross-sectional view showing a state in which a filler is dispersed in a thin film in an example. [Figure 4] FIG. 10 is an enlarged cross-sectional view showing a state in which sheared masses of graphite are generated by sliding between the sliding surface of a rotary seal ring on which a thin film is formed and the sliding surface of a stationary seal ring in the example. [Figure 5] FIG. 10 is an enlarged cross-sectional view showing a state after sliding between the sliding surface of the rotary seal ring on which the thin film is formed and the sliding surface of the stationary seal ring in the embodiment. DETAILED DESCRIPTION OF THE INVENTION

[0011] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS A sliding element according to an embodiment of the present invention will be described below with reference to the accompanying drawings. [Example]

[0012] A sliding component according to an embodiment will be described with reference to Fig. 1 to Fig. 5. In this embodiment, the sliding component will be described as a mechanical seal. The inner diameter side of the sliding component constituting the mechanical seal will be described as the low-pressure fluid side (leak side), and the outer diameter side will be described as the high-pressure fluid side (sealed gas side) (sealed fluid side).

[0013] The mechanical seal for general industrial machinery shown in Figure 1 is an inside type that seals against gas leaking from the outer diameter side of the sliding surface to the inner diameter side in a non-lubricated environment where no liquid is present between the sliding surfaces, i.e., in a dry environment.

[0014] The mechanical seal is primarily composed of a rotary seal ring 20 as a sliding component and a stationary seal ring 10 as another sliding component. The rotary seal ring 20 is annular and is mounted on a rotary shaft 1 via a sleeve 2 so that it can rotate together with the rotary shaft 1. The stationary seal ring 10 is annular and is mounted on a seal cover 5 fixed to a housing 4 of the device to which it is attached so that it can move axially but not rotate. The stationary seal ring 10 is axially biased by a spring 6, so that the sliding surface 11 of the stationary seal ring 10 and the sliding surface 21 of the rotary seal ring 20 slide closely against each other. A gasket 7 seals between the rotary seal ring 20 and the sleeve 2, and an O-ring 8 seals between the stationary seal ring 10 and the seal cover 5.

[0015] In this embodiment, the stationary seal ring 10 and the rotating seal ring 20 are made of silicon carbide (SiC). The stationary seal ring 10 and the rotating seal ring 20 do not have to be made of the same material, and may be made of different materials.

[0016] As shown in Fig. 2, the rotary seal ring 20 is configured by directly coating a thin film 30 on a SiC substrate 22 as a base material. In other words, the actual sliding surface 21 of the rotary seal ring 20 is configured by the surface 30a of the thin film 30. In this embodiment, no thin film is formed on the sliding surface 11 of the stationary seal ring 10 as the mating sliding surface (see Fig. 4).

[0017] In this embodiment, the sliding surface 21 is described as being such that the thickness of the thin film 30 is thicker than the surface roughness of the SiC substrate 22, and the entire surface of one axial end face 22a of the SiC substrate 22 is covered with the thin film 30, as will be described later. However, the present invention is not limited to this. For example, by forming the thin film 30 to be thin, the sliding surface 21 may be such that part of the end face 22a of the SiC substrate 22, such as the top of the mountain on the surface, is exposed and not covered with the thin film 30.

[0018] Furthermore, since the thin film 30 is directly coated on the SiC substrate 22, there is no need to take the time to form an intermediate layer, as compared to when an intermediate layer is used, and there are no restrictions on the conditions of use that are tailored to the intermediate layer.

[0019] The term "thin" in "thin film" means that the film is thinner than the substrate.

[0020] In addition, in this embodiment, the thin film 30 has a layered structure with a carbon atom skeletal structure containing graphite as the main component as the base material, and the thin film 30 contains a high-hardness filler 40 and a low-friction filler 41 as fillers.

[0021] Graphite is a type of carbon material that is mainly composed of carbon atoms and has a hexagonal crystal structure, and is a substance that can be analyzed by Raman spectroscopy and the like.

[0022] Specifically, the thin film 30 of this example is a thin film mainly composed of graphite, i.e., a thin film having a composition in which the characteristics of the graphite component of the skeletal structure of carbon atoms on the surface are prominently exhibited. In the thin film 30, the carbon atoms that mainly constitute graphite form a sheet-like crystalline structure arranged in a hexagonal system through covalent bonds, and the thin sheet-like crystalline structure is bonded in layers by van der Waals forces to form graphite layers. Note that some of the carbon atoms in the skeletal structure may form regions composed of non-graphitized carbon.

[0023] The thin film 30 is formed by directly applying a polyamic acid varnish, which is a precursor solution obtained by dissolving a thermosetting polyimide resin in an organic solvent, to one axial end face 22a of the SiC substrate 22 constituting the rotary seal ring 20 using an application device such as a bar coater or spin coater, and then imidizing the varnish by drying and curing, followed by heating and curing at a temperature of 1200°C or higher in an inert atmosphere and further baking to form a graphitized skeleton. In other words, the carbon atom skeleton structure in the thin film 30 is derived from polyamic acid.

[0024] By forming the thin film 30 to have a thickness within a predetermined range, it is possible to prevent the film from breaking, and the thermosetting resin can be graphitized by baking at a relatively low temperature. Furthermore, the thin film 30 before initial use may be formed to have a thickness of 1 μm to 100 μm. If the film thickness is thinner than the above value, peeling occurs between the SiC substrate 22, and if the film thickness is thicker than the above value, cracks occur during film formation. Furthermore, it is advisable to set the film thickness of the thin film 30 to an optimal value depending on the particle size of the filler and additives dispersed in the film.

[0025] Furthermore, the end surface 22a of the SiC substrate 22 coated with the thin film 30 has an arithmetic mean roughness Ra of 0.1 μm or more on its surface, and the thin film 30 is formed in a state where a portion of the thin film 30 penetrates into the minute recesses 22b of the end surface 22a of the SiC substrate 22.

[0026] Furthermore, the hardness of the thin film 30 and the SiC substrate 12 was measured using a nanoindenter, and it was confirmed that the SiC substrate 12 exhibited a harder value than the thin film 30 .

[0027] As described above, the thin film 30 of this embodiment is formed by baking a thermosetting polyimide resin at a temperature of 1200° C. or higher, and has graphite regions formed on the surface. The composition of the thin film 30 can be determined by analyzing the composition of the film using, for example, XRD, Raman spectroscopy, or thermal analysis.

[0028] Moreover, the thin film 30 is preferably formed by baking a polyimide resin, which is a thermosetting resin, at a temperature of 1200°C or higher and lower than 2000°C.

[0029] As shown in Fig. 3, the thin film 30 has granular high-hardness filler 40 and low-friction filler 41 dispersed substantially uniformly throughout the film, with dimensions equal to or smaller than the thickness of the thin film 30. For ease of explanation, the high-hardness filler 40 and the low-friction filler 41 are shown with the same particle size in Fig. 3. The filler may also be a nanofiller.

[0030] In this embodiment, coke, which is harder than the graphite constituting the thin film 30 and softer than the SiC substrate 12 constituting the opposing sliding surface, was used as the high-hardness filler 40. Note that, other than coke, fillers such as carbon black (CB), carbon fiber (CF), activated carbon, graphite powder, etc. may also be used as the high-hardness filler 40.

[0031] In addition, the hardness of the high-hardness filler 40 was measured using a nanoindenter, and it was confirmed that the high-hardness filler 40 exhibited a harder value than the graphite that constitutes the thin film 30, and a softer value than the SiC substrate 12.

[0032] Furthermore, it is preferable that the content of the high-hardness filler 40 in the thin film 30 is adjusted to 1 to 50 wt %.

[0033] In this embodiment, kaolin clay, which has a lower friction coefficient than the graphite constituting the thin film 30, was used as the low-friction filler 41.

[0034] The coefficient of friction between the thin film 30 and the low-friction filler 41 was measured by conducting a test to measure friction force using an AFM (atomic force microscope), and it was confirmed that the coefficient of friction of the low-friction filler 41 was smaller than that of the graphite that makes up the thin film 30.

[0035] The thin film 30 of this embodiment contains a high-hardness filler 40 as the main filler, which increases the abrasion resistance of the thin film 30, which is mainly made of graphite, and a small amount of a low-friction filler 41 is added to reduce the coefficient of friction on the surface of the thin film 30. The use of kaolin clay as the low-friction filler 41 reduces the coefficient of friction, especially in dry environments.

[0036] Furthermore, it is preferable that the total content of the filler contained in the thin film 30 is 75% by weight or less in order to obtain the low friction effect due to the self-lubricating properties of the graphite.

[0037] Furthermore, the type, number, and content of fillers contained in the thin film 30 may be freely changed depending on the properties required for the sliding surface 21. For example, by adding cerium oxide as a filler in addition to the high-hardness filler 40 and low-friction filler 41 described above, silicate deposits caused by long-life coolant (LLC) can be removed. Furthermore, by adding carbon nanotubes (CNTs) or natural graphite as a filler, electrical properties can be imparted to the thin film.

[0038] The graphitization degree of the surface of the thin film 30 was analyzed using a spectrophotometer manufactured by Nanophoton Co., Ltd., with a central wave number of 2082.24 cm -1 The measurements were performed at an excitation wavelength of 532.36 nm and a laser intensity of 0.8 mW. IG was measured at a central wavenumber of 1574–1576 cm -1 The intensity of the G peak appears at the center wavenumber of 1344-1348 cm. -1 The intensity ratio ID / IG is the intensity of the D peak that appears in the graphite of the present invention. Measurements are taken at multiple points in a specific region of a sample, and the intensity ratio ID / IG is calculated from the G and D peak intensities of the averaged spectrum. If this value is 1 or less, it represents the graphite of the present invention.

[0039] Next, the results of a ring-on-ring friction and wear test conducted under the following conditions on the rotary seal ring 20 on which the thin film 30 was formed will be described. As mentioned above, the stationary seal ring 10 is not formed with a thin film, and at least the sliding surface 11 is made of SiC.

[0040] Load = 10N Surface pressure on the sliding surface of the stationary seal ring = 0.25 MPa Rotating seal ring speed = 74 rpm PV value = 0.008MPa.m / sec Test time = Until the sliding distance reaches 1000m Sealed fluid = atmosphere

[0041] The results of the thin film 30 formation and ring-on-ring friction and wear test on the rotary seal rings 20 (samples F to M) in this example are shown in Table 1. Regarding the ring-on-ring friction and wear test, usability was determined based on whether or not seizure occurred on the sliding surface in a non-lubricated environment. Furthermore, after the ring-on-ring friction and wear test, the thin film 30 was checked for peeling and cracks from the sliding surface 21 of the rotary seal ring 20. To check for peeling, air was sprayed onto the sliding surface 21 of the rotary seal ring 20 to remove any deposits. If the remaining thin film 30 in the minute recesses 22b of the end face 22a was 80% or less of the area within the contact range under a 5x optical microscope, it was determined that peeling had occurred from the sliding surface 21 of the rotary seal ring 20. To check for cracks in the thin film, air was sprayed onto the sliding surface 21 of the rotary seal ring 20 to remove any deposits, and the presence of cracks was confirmed.

[0042] [Table 1]

[0043] In a non-lubricated environment, the thin film 30 of the rotating seal ring 20, which did not experience seizure of the sliding surface and did not peel or crack from the sliding surface 21 of the rotating seal ring 20, was found to have a thickness of 1 μm to 100 μm (samples F, G, H, I, and K).

[0044] Next, the rotary seal rings 20 formed with the thin film 30 of this embodiment were fabricated with different content (weight %) of high-hardness filler 40 in the film, and the results of ring-on-ring friction and wear tests conducted under the following conditions will be described. The thin film 30 of the rotary seal rings 20 was formed with a uniform thickness of 20 μm. The thin film 30 was also formed with a uniform content of low-friction filler 41 of 5 weight %. The stationary seal ring 10 was also formed without a thin film, as described above, with at least the sliding surface 11 being made of SiC.

[0045] Load = 10N Surface pressure on the sliding surface of the stationary seal ring = 0.25 MPa Rotating seal ring speed = 74 rpm PV value = 0.008MPa.m / sec Test time = Until the sliding distance reaches 1000m Sealed fluid = atmosphere

[0046] The results of the ring-on-ring friction and wear test on the rotating seal ring 20 (samples N to S) in this example are shown in Table 2. Regarding the ring-on-ring friction and wear test, usability was judged based on whether or not seizure of the sliding surface occurred in a non-lubricated environment. Furthermore, after the ring-on-ring friction and wear test, the presence or absence of cracks in the thin film 30 on the sliding surface 21 of the rotating seal ring 20 was confirmed in the same manner as in Table 1.

[0047] [Table 2]

[0048] It was found that the thin film 30 of the rotating seal ring 20, which did not experience seizure on the sliding surface and had no cracks in a non-lubricated environment, contained 10% by weight or more of high-hard filler 40, and the total content of high-hard filler 40 and low-friction filler 41 was 30% by weight or less (samples O, P, Q, and R).

[0049] In addition, when the sliding surface 21, on which the thin film 30 is not formed, is opposed to the mating stationary seal ring 10, which is made of a soft material, carbon, foreign matter entering between the sliding surfaces 11, 21 can bite into the sliding surface 11 of the stationary seal ring 10, which is made of soft carbon, and abrade the sliding surface 11, causing surface roughness, resulting in a loss of smoothness and an adverse effect on the coefficient of friction. Thus, the sliding surfaces of sliding components made of carbon have problems with foreign matter resistance. In contrast, in this embodiment, the rotating seal ring 20 is configured by coating the hard SiC substrate 22 with the thin film 30, and the mating stationary seal ring 10 is also made of a hard material, SiC. Therefore, when foreign matter enters between the sliding surfaces 11, 21, the graphite region of the thin film 30 is preferentially abraded, making it less likely that the surface roughness of the SiC substrates 12, 22, which would adversely affect the coefficient of friction of the sliding surfaces, will occur.

[0050] As described above, the SiC substrate 22 of the rotating seal ring 20 according to the present invention is directly coated with the thin film 30, which is primarily made of graphite and contains the high-hardness filler 40 and the low-friction filler 41. Due to friction with the sliding surface 11 of the stationary seal ring 10, the thin film 30, which is primarily made of graphite and which constitutes the sliding surface 21, is sheared between the graphite layers, which are bonded by weak van der Waals forces (see the enlarged portion of FIG. 4). The pressure between the sliding surfaces 11, 21 causes the thin film 30 to be pressed axially, and some of the thin film 30 enters and remains in the minute recesses 22b on the end surface 22a of the SiC substrate 22, smoothing the sliding surface 21 (see the enlarged portion of FIG. 5). This allows the thin film 30 remaining in the minute recesses 22b to exert the self-lubricating properties of graphite on the sliding surface 11 of the stationary seal ring 10, thereby achieving a stable low-friction effect over a wide range of operating conditions, including hydrodynamic lubrication, boundary lubrication, and non-lubricated environments.

[0051] Additionally, the sliding surface 21 of the rotary seal ring 20 coated with the thin film 30 is provided with the added functionality of the high-hardness filler 40 and low-friction filler 41, which are smaller in size than the thickness of the thin film 30. Even with a thin thin film 30, the high-hardness filler 40 and low-friction filler 41 are less likely to fall off, and in particular, the high-hardness filler 40 is prevented from protruding from the sliding surface 21, making it less likely that the sliding surface 11 of the stationary seal ring 10 will be damaged by friction. The thin film 30 also has a high ability to retain particles such as fillers. Falling off of carbon-based fillers in particular can be prevented, even in dry environments.

[0052] Furthermore, the thin film 30 contains a high-hardness filler 40 that is harder than the graphite that constitutes the thin film 30, thereby improving the wear resistance and foreign matter resistance of the sliding surface 21 that is constituted by the thin film 30 that is mainly composed of graphite.

[0053] Furthermore, the graphite region of the thin film 30 wears preferentially over the high-hardness filler 40, forming irregularities on the sliding surface 21, thereby forming roughness on the sliding surface 21. As a result, the convex portions formed on the sliding surface 21 support the load, while the fluid enters the concave portions, particularly during fluid lubrication, promoting lubrication and preventing squealing due to sliding.

[0054] Furthermore, the sheared clumps P30 of graphite derived from the thin film 30 are present in the fluid, thereby improving the lubricity.

[0055] Furthermore, since the high-hardness filler 40 is softer than the sliding surface 11 of the stationary seal ring 10, it is less likely to damage the mating sliding surface 11 due to friction.

[0056] Furthermore, the thin film 30 contains low-friction filler 41 that has a smaller friction coefficient than the graphite that constitutes the thin film 30, thereby making it possible to increase the lubricity of the sliding surface 21.

[0057] Furthermore, because the thin film 30 is formed only on the sliding surface 21 of the rotary seal ring 20, sheared clumps P30 of graphite originating from the thin film 30 that are generated between the sliding surfaces 11, 21 (see the enlarged portion in FIG. 4) are pushed axially by the pressure between the sliding surfaces 11, 21, enter into the minute recesses 12b in the end surface portion 12a of the SiC substrate 12 that constitutes the sliding surface 11 of the stationary seal ring 10, and are transferred to form a transferred film 31, which also smooths the sliding surface 11 of the stationary seal ring 10 (see the enlarged portion in FIG. 5). This increases the proportion of sliding portions between SiC and graphite, or between graphite and graphite, between the sliding surfaces 11, 21, and provides a better low-friction effect.

[0058] Furthermore, the thin film 30 is formed by directly applying polyamic acid varnish, a precursor solution obtained by dissolving a thermosetting polyimide resin in an organic solvent, to the end surface 22a of the SiC substrate 22 and then baking it. This allows the polyamic acid varnish to penetrate into the minute recesses 22b in the end surface 22a of the SiC substrate 22, thereby enhancing adhesion of the thin film 30 to the SiC substrate 22. Furthermore, by adjusting the viscosity of polyamic acid varnish, a precursor solution of polyimide resin with excellent film-forming properties, and applying and forming the polyamic acid varnish, the thin film 30 shrinks favorably in the planar and thickness directions, improving adhesion. Therefore, there is no limit to the area of ​​the thin film 30 that can be formed.

[0059] Furthermore, since the thin film 30 is directly coated on the SiC base material 22, frictional heat generated by relative sliding with the mating sliding surface 11 is directly transferred from the thin film 30 to the SiC base material 22, thereby suppressing a temperature rise on the sliding surface 21.

[0060] Furthermore, while graphite is usually produced at an extremely high temperature of about 3000°C, the thin film 30 of the present invention can be produced by applying a thin layer of polyamic acid varnish and baking it at a relatively low temperature of 1200°C or higher but lower than 2000°C. Therefore, peeling or tearing of the thin film 30 due to thermal shrinkage is unlikely to occur, the thin film 30 is easy to process, and the sliding surface 21 can exhibit excellent self-lubricating properties due to the graphite.

[0061] Furthermore, the thin film 30 is formed to a thickness of 1 μm to 100 μm, and contains filler with dimensions equal to or smaller than the thickness of the thin film 30, which allows gas generated inside the thin film 30 during firing to escape more easily, thereby preventing cracks from occurring.

[0062] Furthermore, because the hardness of the thin film 30 is less than the hardness of the sliding surface 11 of the stationary seal ring 10, i.e., the SiC substrate 12, the thin film 30 is softer than the sliding surface 11 of the stationary seal ring 10 and is less likely to damage the sliding surface 11 of the stationary seal ring 10 due to friction. Furthermore, because the hardness of the thin film 30 is less than the hardness of the SiC substrate 22 of the rotary seal ring 20, if a foreign object enters between the sliding surfaces 11, 21, the graphite region of the soft thin film 30 is preferentially sheared, promoting the smoothing of the sliding surface 21, and the exposed end surface 22a of the hard SiC substrate 22 and the high-hardness filler 40 can improve foreign object resistance, so that the self-lubricating properties of graphite and foreign object resistance can both be achieved between the sliding surfaces 11, 21.

[0063] Furthermore, the substrate of the rotary seal ring 20 is made of SiC, a ceramic, and because the SiC substrate 22 is porous, there are many fine recesses 22b on the end surface 22a into which part of the thin film 30 enters, and because this is more likely to produce surface roughness than metal, the thin film 30 is easily attached to the substrate surface. Furthermore, the end surface 22a of the SiC substrate 22 on which the thin film 30 is formed has an arithmetic mean roughness Ra of 0.1 μm or more, which makes it easier for part of the thin film 30 to enter into the fine recesses 22b on the end surface 22a. Therefore, even if the graphite region of the thin film 30 is sheared by friction with the sliding surface 11 of the stationary seal ring 10, part of the thin film 30 is held in the fine recesses 22b and is less likely to fall off from between the sliding surfaces 11, 21.

[0064] Furthermore, the end surface 22a of the SiC substrate 22 is entirely covered with the thin film 30. In other words, the substrate surface is not exposed, and therefore, a portion of the thin film 30 penetrates into all of the minute recesses 22b in the end surface 22a. As a result, the graphite region of the thin film 30 is sheared, and the sliding surface 21 is easily smoothed.

[0065] Furthermore, since the thin film 30 has a thickness of 1 μm to 100 μm, peeling of the thin film 30 from the end surface portion 22a of the SiC substrate 22 and cracks occurring in the thin film 30 can be prevented, and therefore the thin film 30 can be used as a film for sliding parts.

[0066] Furthermore, the thickness of the thin film 30 is greater than the arithmetic mean roughness Ra of the surface of the end face portion 22a of the SiC substrate 22, i.e., the thickness of the thin film 30 is greater than the unevenness of the surface of the end face portion 22a of the SiC substrate 22. As a result, a portion of the thin film 30 is likely to enter the fine recesses 22b of the SiC substrate 22, and the graphite region of the thin film 30 is reliably sheared by friction with the sliding surface 11 of the stationary seal ring 10, so that a portion of the thin film 30 is likely to remain in the fine recesses 22b, and a low-friction effect is easily achieved.

[0067] Furthermore, because the base material and sliding surface of the rotating seal ring 20 can be made of different materials, the base material can have the rigidity and high thermal conductivity of ceramics such as SiC, while the thin film 30 on the sliding surface 21 can have the self-lubricating properties of graphite and the functionality of various fillers. Furthermore, by changing the base material to a cheaper material, the cost of the sliding parts can be reduced.

[0068] Furthermore, since the thin film 30 is mainly composed of graphite, it also has excellent chemical resistance and oxidation resistance. The oxidation resistance of the thin film 30 is at the same level as that of highly crystalline artificial graphite for electrodes, indicating that high crystallinity can be obtained at a relatively low temperature.

[0069] Although the embodiments of the present invention have been described above with reference to the drawings, the specific configuration is not limited to these embodiments, and the present invention also includes modifications and additions that do not deviate from the gist of the present invention.

[0070] For example, in the above embodiment, a mechanical seal for general industrial machinery was used as an example of the sliding component, but other mechanical seals for automobiles, water pumps, etc. may also be used. Furthermore, the present invention is not limited to mechanical seals, and may also be applied to sliding components other than mechanical seals, such as plain bearings. Furthermore, since the thin film 30 can be formed on the inner peripheral surface of a bearing, it can also be applied to sliding components that constitute radial bearings, etc.

[0071] Furthermore, in the above-described embodiment, the mechanical seal to which the sliding parts are applied is described as being used in a non-lubricated environment, but this is not limiting and the mechanical seal may be used in a fluid lubrication region or a boundary lubrication region where a liquid, which is a sealed fluid, is interposed between the sliding surfaces.

[0072] In addition, in the above embodiment, an example was described in which the thin film 30 was provided only on the rotary seal ring 20, but the thin film 30 may be provided only on the stationary seal ring 10, or may be provided on both the rotary seal ring 20 and the stationary seal ring 10.

[0073] In the above embodiment, the thin film 30 is described as being derived from polyamic acid, which is a precursor solution obtained by dissolving polyimide resin in an organic solvent. However, the present invention is not limited to this. The thin film may be derived from a precursor solution obtained by dissolving one or more thermosetting resins selected from phenolic resin, melamine resin, urea resin, epoxy resin, unsaturated polyester resin, silicone resin, diallyl phthalate resin, polyimide resin, polyurethane resin, etc., in an organic solvent.

[0074] The filler is not limited to granular fillers, but may be fibrous fillers, for example.

[0075] Furthermore, thin film 30 does not need to contain low-friction filler 41 as long as sufficient lubrication can be obtained on sliding surface 21 due to the self-lubricating properties of graphite.

[0076] In the above example, the graphitization degree of the thin film 30 is changed by changing the firing temperature within a range of 1200° C. or more and less than 2000° C. and firing for 30 minutes in a nitrogen atmosphere. However, the present invention is not limited to this. The graphitization degree may be changed by setting the firing temperature to the same temperature within a range of 1200° C. or more and less than 2000° C. and changing the firing time.

[0077] Furthermore, the arithmetic mean roughness Ra of the surface of the end face 22a of the SiC base material 22 covered with the thin film 30 may be 0.1 μm or less depending on the thickness of the thin film 30.

[0078] In the above embodiment, the stationary seal ring 10 and the rotating seal ring 20 are described as being made of SiC, but this is not limiting and any sliding material used as a sliding material for mechanical seals can be used. SiC may be a sintered body using boron, aluminum, carbon, or other sintering aids, or a material consisting of two or more phases with different components or compositions, such as SiC with dispersed graphite particles or reaction-sintered SiC consisting of SiC and Si. In addition to the above sliding materials, other ceramics such as alumina, zirconia, and silicon nitride (Si3N4), metal materials, resin materials, composite materials, and the like can also be used.

[0079] For example, when the base material of a sliding part is made of partially stabilized zirconia, the base material itself has excellent toughness but poor thermal conductivity. However, since the graphite region of the thin film 30 that covers the sliding surface has excellent thermal conductivity in the planar direction, frictional heat generated by relative sliding with the opposing sliding surface can be dissipated in the planar direction, thereby suppressing the temperature rise of the sliding surface. [Explanation of symbols]

[0080] 10 Stationary seal ring (sliding part) 11 Sliding surface 12 SiC base material (base material) 12a End face part 12b Micro recess 20 Rotating seal ring (sliding part) 21 Sliding surface 22 SiC base material (base material) 22a End face part 22b Micro recess 30 Thin Film 30a surface 31 Transfer membrane 40 High hardness filler (filler) 41 Low friction filler (filler) P30 Shear mass

Claims

1. A sliding component having a sliding surface that slides relative to one another, a substrate of the sliding component is directly coated with a thin film mainly made of graphite, the sliding surface is made of the thin film, and the thin film contains a filler having a size equal to or smaller than the thickness of the thin film; The filler includes a high-hardness filler that is harder than the graphite and a low-friction filler that has a friction coefficient smaller than that of the graphite, the content of the high hardness filler in the thin film is 1 to 50% by weight, A sliding component, wherein the content of the low friction filler in the thin film is lower than the content of the high hard filler.

2. 2. The sliding component according to claim 1, wherein the hardness of the high-hardness filler is lower than the hardness of the mating sliding surface.

Citation Information

Patent Citations

  • Slide part

    JP2004225725A

  • Refrigerating unit

    JP2008128220A

  • Composite material, manufacturing method of the composite material and slide member using the composite material

    JP2009091661A

  • Dry contact mechanical seal

    JP2011058517A

  • Mechanical seal

    JP2019015309A